Patient-reported negative experiences related to caries and its treatment among Swedish adult patients - Flink, Håkan; Tegelberg, Åke; Arnetz, Judith E.; Birkhed, Dowen (BMC Oral Health, 2017)
It has been suggested that dental caries should be regarded as a chronic disease as many individuals repeatedly develop new caries lesions. How this is perceived by caries active patients is unclear. The aim of this study was to measure patient-reported attitudes and negative experiences related to caries and dental treatment.